2013
DOI: 10.1163/15685411-00002717
|View full text |Cite
|
Sign up to set email alerts
|

Description of Schistonchus superbus n. sp. (Nematoda: Aphelenchoididae), an associate of Ficus superba in China

Abstract: A new nematode species was recovered from the syconia of Ficus superba from the South China Botanical Garden, Chinese Academy of Sciences, Guangzhou, Guangdong Province, China, during a survey of nematode biodiversity from 2007 to 2012. It is described herein as Schistonchus superbus n. sp. and is characterised by possessing the combined characters of a short post-uterine sac and digitate tail without a mucron in females, excretory pore located near the metacorpus, amoeboid sperm, a unique wedge-shaped male ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…is very similar to that of B. sycophilus , i.e., it has a long conus and distinct basal swellings. Interestingly, the genus is clearly paraphyletic [69] [71] ( Fig. 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…is very similar to that of B. sycophilus , i.e., it has a long conus and distinct basal swellings. Interestingly, the genus is clearly paraphyletic [69] [71] ( Fig. 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ficus altissima is a member of the monoecious subgenus Schistonchus Cobb, 1927 (Aphelenchoididae) has long been recognised as associated with fig wasps and fig sycones (Gasparrini 1864). So far, 21 species of Schistonchus have been described from Ficus species from Central America, North America, Asia, Africa and Australia (Anand, 2002;Bartholomaeus et al 2012;Cobb 1927;Davies et al 2010Davies et al , 2013DeCrappeo & Giblin-Davis 2001;Kumari & Reddy 1984;Reddy & Rao, 1984;Vovlas et al 1998;Zeng et al 2007Zeng et al , 2010Zeng et al , 2011Zeng et al , 2013aZeng et al , 2013b. A recent survey on the diversity of fig nematodes in Guangdong Province, China revealed an undescribed species of nematode from F. altissima in the residential area of Huajingxincheng, Guangzhou, Guangdong Province, China.…”
Section: Introductionmentioning
confidence: 99%
“…Martin et al (1973) reported a variety of different ne matode types associated with figs in tropical Africa, but provided few taxonomic details. Two nematode genera, Schistonchus Cobb, 1927(Fuchs, 1937) (Aphelenchoididae) and Parasitodiplogaster Poinar, 1979 (Diplogastridae), are well known from inside the sycones of Ficus species worldwide (Gasparrini, 1864;Poinar, 1979;Kumari & Reddy, 1984;Reddy & Rao, 1984;Poinar & Herre, 1991;Giblin-Davis et al, 1995, 2003, 2006Lloyd & Davies, 1997;DeCrappeo & Giblin-Davis, 2001;Anand, 2002;Zeng et al, 2007Zeng et al, , 2010Zeng et al, , 2011Zeng et al, , 2013aBartholomaeus et al, 2009Bartholomaeus et al, , 2012Davies et al, 2009Davies et al, , 2010Kanzaki et al, 2010Kanzaki et al, , 2012Kanzaki et al, , 2013Kanzaki et al, , 2014aWohr et al, 2014). Schistonchus is a polyphyletic plant-parasitic nematode grouping in the Aphelenchoididae that feeds and reproduces on the epidermis of florets inside the sycone and is an internal phoretic of its fig wasp pol linator host which transports it to the next suitable fig (Vovlas etal., 1992(Vovlas etal., , 1996Giblin-Davis etal., 1995;Cen ter et al, 1999;Davies et al, 2010).…”
mentioning
confidence: 99%
“…Schistonchus is a polyphyletic plant-parasitic nematode grouping in the Aphelenchoididae that feeds and reproduces on the epidermis of florets inside the sycone and is an internal phoretic of its fig wasp pol linator host which transports it to the next suitable fig (Vovlas etal., 1992(Vovlas etal., , 1996Giblin-Davis etal., 1995;Cen ter et al, 1999;Davies et al, 2010). This genus cur rently contains 25 nominal species (Zeng et al, 2013a). Parasitodiplogaster is an apparently parasitic or possi bly necromenic nematode associate that develops in its fig wasp pollinator host before leaving to mate and pro duce infective juveniles inside the fig that infect the next generation of wasps as they leave for a new fig (Poinar & Herre, 1991;Giblin-Davis et al, 1995, 2006Kan zaki et al, 2010Kan zaki et al, , 2012Kan zaki et al, , 2013Kan zaki et al, , 2014a.…”
mentioning
confidence: 99%